Factors influencing the quality of life of stroke patients - Nayeem, A; Anwarullah, AKM; Sardar, MH; Hossain, MZ; Zaman, F; Islam, MN (Journal of Dhaka Medical College, 2013)
DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13230 J. Dhaka Med. Coll. 2012; 21(1): 3-7